Implementing 12345 Fit-Tastic: A Tool for Combating Childhood Obesity. (March 2016) - Wade, Kerri; Summar, Shelly; Dewit, Emily
Childhood obesity is epidemic in the United States. School nurses are in a unique position to address weight with the students they serve. This article provides tools for school nurses to be able to conduct an obesity screening, demonstrate the basic skills of motivational interviewing in treatment of obesity in a school age child, and utilize the 12345 Fit-Tastic program in their practice. This article is the seventh and final article in a series on the topic of childhood obesity and the accompanying comorbidities.